USE OF EDUCATIONAL TECHNOLOGY IN COOPERATION IN STUDENT EDUCATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article highlights the growing interest and interest of the new pedagogical technologies in the learning process today, in the elementary education that forms the basis of secondary schools. The use of pedagogical technologies in the process of teaching science provides guidelines on the ways in which pupils can deepen their profound learning.